2017
DOI: 10.1016/j.psychres.2017.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptoms and response quality to self-rated personality tests: Evidence from the PsyCoLaus study

Abstract: Despite the fact that research has demonstrated consistent associations between self-rated measures of personality dimensions and mental disorders, little has been undertaken to investigate the relation between psychiatric symptoms and response patterns to self-rated tests. The aim of this study was to investigate the association between psychiatric symptoms and response quality using indices from our functional method. A sample of 1,784 participants from a Swiss population-based cohort completed a personality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In terms of theoretical mechanisms, it is possible that there is an interplay between psychopathological symptomology and the properties of internal consistency reliability: it has been shown that reliability of a self-report Likert scale may be affected by “insufficient effort responding” (careless responding styles), for example by “straightlining” identical responses or giving random ratings [ 37 ], resulting in biased estimates of internal consistency [ 38 ]. Accordingly, recent research has shown that psychiatric symptoms are associated with less consistent response patterns on self-rated scales [ 39 ]. Consequently, we argue that the potential heterogeneity across pre- and post-treatment reliability estimates might be attributed to depression-related psychopathology (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of theoretical mechanisms, it is possible that there is an interplay between psychopathological symptomology and the properties of internal consistency reliability: it has been shown that reliability of a self-report Likert scale may be affected by “insufficient effort responding” (careless responding styles), for example by “straightlining” identical responses or giving random ratings [ 37 ], resulting in biased estimates of internal consistency [ 38 ]. Accordingly, recent research has shown that psychiatric symptoms are associated with less consistent response patterns on self-rated scales [ 39 ]. Consequently, we argue that the potential heterogeneity across pre- and post-treatment reliability estimates might be attributed to depression-related psychopathology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability estimates were calculated pre- and post-treatment to allow for the detection of potential effects of psychiatric symptom burden on internal consistency. There is preliminary evidence that careless response styles are common in psychiatric patients, which in turn may affect internal consistency estimates of Likert scales (see discussion below) [ 37 39 ]. Accordingly, we expected appropriate post-treatment reliabilities for all scales (ω ≥ .70) and hypothesized a qualitative trend towards lower estimates for the pre-treatment condition.…”
Section: Introductionmentioning
confidence: 99%
“…20 Participants were reassessed approximately 5 (Follow-up 1, FU1) and 10 years (Follow-up 2, FU2) after the first investigation at baseline. 16,17 The present analyses are based on data from the first and second follow-ups. FU1 was carried out between 2009 and 2013, and FU2 between 2013 and 2017.…”
Section: Participantsmentioning
confidence: 99%
“…The study included a relatively homogenous sample of severely depressed patients and did not recruit patients from ambulatory settings with lower fatigue symptom severity, which leads to selection bias. Pre-assessments could therefore be subject to insufficient effort responding on self-report measures (e.g., straight lining, random responding), which has been linked to psychiatric symptom burden, and inflates type II errors by decreasing the size of estimated correlations [ 64 , 65 ]. f) “Is the measurement reliability for either variable (or both) low?” (p. 264).…”
Section: Discussionmentioning
confidence: 99%